Different calcification patterns of tricuspid and bicuspid aortic valves and their clinical impact. (16th November 2022) - Gollmann-Tepeköylü, Can; Nägele, Felix; Engler, Clemens; Stoessel, Leon; Zellmer, Berit; Graber, Michael; Hirsch, Jakob; Pölzl, Leo; Ruttmann, Elfriede; Tancevski, Ivan; Tiller, Christina; Barbieri, Fabian; et al.
Abstract: OBJECTIVES: Mechanical strain plays a major role in the development of aortic calcification. We hypothesized that (i) valvular calcifications are most pronounced at the localizations subjected to the highest mechanical strain and (ii) calcification patterns are different in patients with bicuspid and tricuspid aortic valves. METHODS: Multislice computed tomography scans of 101 patients with severe aortic stenosis were analysed using a 3-dimensional post-processing software to quantify calcification of tricuspid aortic valves (n = 51) and bicuspid aortic valves (n = 50) after matching. RESULTS: Bicuspid aortic valves exhibited higher calcification volumes and increased calcification of the non-coronary cusp with significantly higher calcification of the free leaflet edge. The non-coronary cusp showed the highest calcium load compared to the other leaflets. Patients with annular calcification above the median had an impaired survival compared to patients with low annular calcification, whereas patients with calcification of the free leaflet edge above the median did not ( P = 0.53). CONCLUSIONS: Calcification patterns are different in patients with aortic stenosis with bicuspid and tricuspid aortic valves. Patients with high annular calcification might have an impaired prognosis. Abstract : Aortic valve stenosis represents a major socioeconomic burden in the Western world with a prevalence of 2.8% in >75-year-old individuals and 9.8% in octogenerians [1].